AN ANALYSIS OF THE CULINARY TOURISM EXPERIENCE BETWEEN GENDER GROUPS IN IRAN - Movahed, Ali; Ghasemi, Moslem; Gholamalifard, Nasrin (Quaestiones Geographicae, 2020)
The purpose of this study is to investigate the role of culinary tourism experience between gender groups in Iranian culinary education tours. The research sample was randomly selected from 50 foreign tourists who participated in Persian Food Torus Institute’s culinary tours during four months. Kim et al. (2012) model of Memorable Tourism Experiences (MTEs) is used to design the research questionnaire and data. The results show that there is a significant difference in women’s desire for enjoyment, sense of freedom, power and refreshment rather than men. But in terms of tourism experiencenovelty, local culture, meaningfulness, and knowledge gained for both men and women, it was no difference.